STRATEGI PENGUASAAN FI’IL AMR MELALUI PENDEKATAN KOMUNIKATIF PADA SISWA SEKOLAH DASAR ISLAM TERPADU - Sabrina Ayuning Pawestri; Siti Nurdinah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Mastery of fi'il amr (imperative verbs) is a fundamental Arabic language competency essential for elementary school students' active communication skills. However, its instruction in Islamic Integrated Elementary Schools (SDIT) is still dominated by rote memorization of textual nahwu (grammar) rules, leaving students unable to apply it functionally. Prior studies on the Communicative Language Teaching (CLT) approach have largely focused on general speaking skills at the secondary and higher education levels, while its application to mastering fi'il amr at the elementary level remains understudied. This study offers novelty in the form of a CLT implementation framework specifically designed for teaching fi'il amr in SDIT settings. The study aims to describe the implementation of the communicative approach in mastering fi'il amr among sixth-grade students at SDIT Imam Ahmad, identify its supporting and inhibiting factors, and analyze its impact on students' communication skills. This study employed a descriptive qualitative approach, with Arabic language teachers and sixth-grade students selected purposively as subjects. Data were collected through participatory observation, semi-structured interviews, and documentation, validated using triangulation of techniques, and analyzed using the Miles and Huberman interactive model. The results show that CLT implementation was carried out through three stages: apperception-modeling, pair practice-role play, and reflection-rule reinforcement. Its success was supported by varied instructional media, teachers' ability to integrate approaches, and a school environment conducive to Arabic language habituation, though it still faced linguistic, psychological, and structural challenges. The communicative approach enhanced students' active engagement and functional use of fi'il amr, positioning it as an alternative strategy for more contextual and meaningful Arabic grammar instruction at the elementary level. ABSTRAK Penguasaan fi'il amr merupakan kompetensi dasar bahasa Arab yang penting bagi kemampuan komunikasi aktif siswa sekolah dasar, namun pembelajarannya di SDIT masih didominasi oleh hafalan kaidah nahwu secara tekstual sehingga siswa kurang mampu menerapkannya secara fungsional. Kajian Communicative Language Teaching (CLT) selama ini lebih banyak menyasar keterampilan berbicara secara umum di jenjang menengah dan perguruan tinggi, sementara penerapannya untuk penguasaan fi'il amr di sekolah dasar masih jarang diteliti. Penelitian ini menawarkan kebaruan berupa tahapan implementasi CLT yang dirancang khusus untuk pembelajaran fi'il amr di SDIT. Penelitian bertujuan mendeskripsikan implementasi pendekatan komunikatif dalam penguasaan fi'il amr pada siswa kelas VI SDIT Imam Ahmad, mengidentifikasi faktor pendukung dan penghambatnya, serta menganalisis dampaknya terhadap kemampuan komunikasi siswa. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek guru bahasa Arab dan siswa kelas VI yang dipilih secara purposive. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi, diuji keabsahannya dengan triangulasi teknik, dan dianalisis menggunakan model interaktif Miles dan Huberman. Hasil menunjukkan implementasi CLT dilaksanakan melalui tiga tahap: apersepsi-modeling, pair practice-role play, serta refleksi-penguatan kaidah. Keberhasilannya didukung media pembelajaran variatif, kemampuan guru mengintegrasikan pendekatan, dan lingkungan sekolah yang mendukung pembiasaan bahasa Arab, meski masih terkendala aspek linguistik, psikologis, dan struktural. Pendekatan komunikatif meningkatkan keterlibatan aktif siswa dan penggunaan fi'il amr secara fungsional, sehingga menjadi alternatif strategi pembelajaran tata bahasa Arab yang lebih kontekstual dan bermakna di sekolah dasar.